A C3 continuous toolpath corner smoothing method for a hybrid machining robot. (March 2022) - Liu, Haitao; Li, Guangxi; Xiao, Juliang
Abstract: A high-order continuity of a five-axis toolpath helps avoid problems such as equipment resonance, allowing high-quality and high-efficiency machining to be achieved. This paper presents a semi-analytical C 3 continuous toolpath corner smoothing method for a 5-DOF (degree of freedom) hybrid robot. Based upon curvature derivative continuity conditions, the tool position and orientation paths can be directly smoothed by inserting quintic B-splines. Benefitting from an analytical error expression, orientation error can be accurately predicted and controlled with improved computational efficiency. Then, by converting the remaining position and orientation segments into the specially designed 7th-degree B-spline, the C 3 continuity of the geometrically smoothed toolpath is mathematically guaranteed without iterative calculations. Additionally, a path adjustment strategy is developed to enhance the performance of the proposed approach. Finally, simulations and experiments are carried out on the TriMule-800 mobile robot machining system by incorporating a jerk-continuous feedrate profile. The feasibility of the proposed approach in addressing a general five-axis toolpath is verified. Highlights: A C 3 continuous corner smoothing method for the five-axis linear toolpath is proposed. A control point formulation strategy is developed for direct orientation path smoothing. Parameter synchronization is achieved by converting the remaining path segments into 7th-degree B-splines. An effective adjustment of the geometric toolpath is applied to improve the trajectory smoothness. The effectiveness of the proposed method is verified by simulations and experiments on the TriMule-800 hybrid robot.